Characterization of Sandwich Structured Composites between Rice Flour-based Thermoplastic Starch and Rice Straw - Kengkhetkit, Nanthaya; Wongpreedee, Thapanee (Recent Science and Technology, 2023)
The sandwich structured composites with rice flour-based thermoplastic starch (TPS) and rice straw (RS) were prepared. The effects of different TPS types (glutinous rice flour (GTPS), rice flour (RTPS), and mixed rice flour (MTPS)) and types of sandwiched composite (3 and 5 layers) on the density and tensile properties of these composites were investigated. The results showed that the density of all RS-TPS composites was lower than each neat TPSs. The differences of TPSs types and sandwiched composite types did not affect the density of these materials. On the contrary, the tensile modulus and tensile strength of all RS-TPS composites showed a strong improvement with an increase up to 193-461% and 111-194%, respectively, compared with each neat TPS. However, the efficiency of composite’s tensile property improvement strongly depended on the TPS types. Composite using GTPS having high melt flow index displayed high potential to improve the tensile properties. The SEM investigation revealed that the GTPS matrix easily flowed and wetted into the RS reinforcement layer during compression. This resulted in enhancing the composite’s tensile properties. In contrast, using RTPS with a low melt flow index in composites did not show evidence of RTPS penetrating into RS layer. So, RS-RTPS composite showed only the improvement in tensile modulus but not in tensile strength. The sandwich composite with three layers showed better improvement in tensile properties compared with five layers in all TPS composite types.